Social climate factors towards depression among Assistant Medical Officers in psychiatric institution - Rueben, Isaac Muthuswami (2024)
The role of Assistant Medical Officers (AMOs) within psychiatric institutions is vital, yet often challenging, as they navigate the complexities of patient care in environments influenced by various social factors. Depression generally exists in every human being, and how well a person manages and exerts control over it varies from person to person. The aim of this research is to investigate the impact of social climate factors towards depression among assistant medical officers in psychiatric instituition. The research design involved in this study is of quantitative type. The design of this study is based on quantitative research because the total number of respondents for this study involves a total of 206 assistants’ medical officer of the Hospital Bahagia, Ulu Kinta, Perak. The sampling size were chosen based on the Krejcie & Morgan, (1970) table of sampling and a total of 136 respondent were chosen. This study uses a set of questionnaires the research instruments. The depression was recorded a high level among the assistant medical officers. The finding also revealed that there is a significant relationship for between all four variables of work life balance, peer support, positive communication as well as flexibility and autonomy towards the depression among assistant medical officer. Overall, all four hypotheses are accepted. The study underscores the importance of addressing work-life balance, peer support, positive communication, flexibility, and autonomy to promote mental well-being among healthcare professionals. The implications of the research are clear: healthcare institutions, professionals, administrators, policymakers, and researchers must prioritize mental health initiatives and collaborate to create supportive work environments that prioritize the mental health and well-being of healthcare professionals. Recommendations for future research include adopting mixed-methods approaches, longitudinal study designs, comparative studies across healthcare professions and settings, exploration of interventions, and collaboration with stakeholders to ensure research findings are relevant and actionable in improving mental health outcomes among healthcare professionals.